A common variant in the ABCA1 gene is associated with a lower risk for premature coronary heart disease in familial hypercholesterolaemia. Issue 3 (1st March 2003) - Cenarro, A; Artieda, M; Castillo, S; Mozas, P; Reyes, G; Tejedor, D; Alonso, R; Mata, P; Pocoví, M; Civeira, F
Abstract : Familial hypercholesterolaemia (FH) is a common autosomal codominant hereditary disease caused by defects in the LDL receptor ( LDLR ) gene, and one of the most common characteristics of affected subjects is premature coronary heart disease (CHD). In heterozygous FH patients, the clinical expression of FH is highly variable in terms of the severity of hypercholesterolaemia and the age of onset and severity of CHD. Identification of mutations in the ATP binding cassette transporter 1 ( ABCA1 ) gene in patients with Tangier disease, who exhibit reduced HDL cholesterol and apolipoprotein A1 concentrations and premature coronary atherosclerosis, has led us to hypothesise that ABCA1 could play a key role in the onset of premature CHD in FH. In order to know if the presence of the R219K variant in the ABCA1 gene could be a protective factor for premature CHD in FH, we have determined the presence of this genetic variant by amplification by PCR and restriction analysis in a group of 374 FH subjects, with and without premature CHD. The K allele of the R219K variant was significantly more frequent in FH subjects without premature CHD (0.32, 95% CI 0.27 to 0.37) than in FH subjects with premature CHD (0.25, 95% CI 0.21 to 0.29) (p<0.05), suggesting that the genetic variant R219K in ABCA1 could influence the development and progression of atherosclerosis in FH subjects. Moreover, the K allele of the R219K polymorphism seems to modify CHD risk without important modification of plasma HDL-C levels, and it appears to be more protective for smokers than non-smokers.